The effects of injury prevention warm-up programmes on knee strength in male soccer players - Daneshjoo, A.; Mokhtar, A. H.; Rahnama, N.; Yusof, A. (Biology of Sport, 2013)
The study investigates the effects of the 11+ and HarmoKnee injury prevention programmes on knee strength in male soccer players. Under-21-year-old players (n=36) were divided equally into: the 11+, HarmoKnee and control groups. The programmes were performed for 24 sessions (20-25 min each). The hamstrings and quadriceps strength were measured bilaterally at 60°.s-1, 180°.s-1 and 300°.s-1 using the Biodex Isokinetic Dynamometer. The quadriceps peak torque (PT) of the 11+ increased by 27.7% at 300°.s-1 in the dominant leg (p<0.05). The quadriceps PT of HarmoKnee increased by 36.6%, 36.2% and 28% in the dominant leg, and by 31.3%, 31.7% and 20.05% at 60°.s-1, 180°.s-1 and 300°.s-1 in the non-dominant leg respectively. In the 11+ group the hamstring PT increased by 22%, 21.4% and 22.1% at 60°.s-1, 180°.s-1 and 300°.s-1, respectively in the dominant leg, and by 22.3%, and 15.7% at 60°.s-1 and 180°.s-1, in the non-dominant leg. In the HarmoKnee group the hamstrings in the dominant leg showed an increase in PT by 32.5%, 31.3% and 14.3% at 60°.s-1, 180°.s-1 and 300°.s-1, and in the non-dominant leg hamstrings PT increased by 21.1% and 19.3% at 60°.s-1 and 180°.s-1 respectively. The hamstrings strength was significantly different between the 11+ and control groups in the dominant (p=0.01) and non-dominant legs (p=0.02). The HarmoKnee programme enhanced the concentric strength of quadriceps. The 11+ and HarmoKnee programmes are useful warm-up protocols for improving concentric hamstring strength in young professional male soccer players. The 11+ programme is more advantageous for its greater concentric hamstring strength improvement compared to the HarmoKnee programme.